The Role of Emotion Regulation and Social Support as Mediators in Gender Differences in Students’ Academic Stress: Peran Regulasi Emosi dan Dukungan Sosial sebagai Mediator Perbedaan Gender dalam Stres Akademik Siswa - M Hubbal Khair; Yeldi Efrianto (Ikhtisar: Jurnal Pengetahuan Islam, 2026)
Academic stress is a psychological condition frequently experienced by students, particularly prior to final examinations, and it can negatively affect both mental health and academic performance. This study aims to examine the role of emotion regulation and social support as mediating variables in the relationship between gender and academic stress. This study employed a quantitative approach using a causal model design with mediation analysis. The sample consisted of 100 students from SMAN 1 Padang Sago, selected using purposive sampling. The instruments included three scales: academic stress (α = 0.87), emotion regulation (α = 0.82), and social support (α = 0.85). Data were analyzed using independent samples t-tests and path analysis, with bootstrapping procedures in SEM to test mediation effects. The results indicated a significant difference in academic stress between male and female students, with female students reporting higher levels of stress. Furthermore, emotion regulation and social support were found to significantly mediate the relationship between gender and academic stress.These findings highlight the importance of gender-sensitive psychological interventions and the strengthening of social support systems in schools to reduce academic stress among students.